2020
DOI: 10.3390/nu12020496
|View full text |Cite
|
Sign up to set email alerts
|

What Serum Sodium Concentration Is Suggestive for Underhydration in Geriatric Patients?

Abstract: Dehydration is a concern among aging populations and can result in hospitalization and other adverse outcomes. There is a need to establish simple measures that can help in detecting low-intake dehydration (underhydration) in geriatric patients. The predictive performance of sodium, urea, glucose, and potassium to discriminate between patients with and without underhydration was evaluated using receiver-operating characteristic (ROC) curve analysis of data collected during the cross-sectional study of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Another interesting aspect of the results of our study is the ability of serum sodium concentration to act as a marker of hypohydration in older adults, as reported by Wojszel, 41 who found that a serum sodium equal to 140 mmol L –1 or higher appeared to be suggestive of impending underhydration in geriatric patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Another interesting aspect of the results of our study is the ability of serum sodium concentration to act as a marker of hypohydration in older adults, as reported by Wojszel, 41 who found that a serum sodium equal to 140 mmol L –1 or higher appeared to be suggestive of impending underhydration in geriatric patients.…”
Section: Discussionsupporting
confidence: 72%
“…Although the sensitivity analysis has shown that, when excluding participants with self-reported renal disease, the results were consistent with the primary analyses, it is worth noting that other causes of excess sodium in the urine, such as mineralocorticoid deficiency, syndrome of inappropriate antidiuretic hormone secretion, hypothyroidism or hypopituitarism, were not considered in the present study. 40 Another interesting aspect of the results of our study is the ability of serum sodium concentration to act as a marker of hypohydration in older adults, as reported by Wojszel, 41 who found that a serum sodium equal to 140 mmol L -1 or higher appeared to be suggestive of impending underhydration in geriatric patients.…”
Section: T a B L Esupporting
confidence: 67%
“…A wide range of ROE (e.g., laboratory reference range, 283-1215 mOsm•24 h −1 for women) is possible in adults, as illustrated in Table 3. Because concentrated urine is a primary etiological factor in kidney stone formation and urinary tract infections [13][14][15][16]28,99,100], it is worthy of future studies that identify ways to simply and effectively reduce ROE.…”
Section: Renal Osmolar Excretion: Differences Due To Dietmentioning
confidence: 99%
“…Similarly, increasing TWI is important for elderly adults who live in geriatric facilities, because dehydration is associated with significant adverse outcomes in older people despite being largely preventable and treatable [121]. For example, two recent European studies published in Nutrients reported that dehydration (P OSM > 295 mOsm•kg −1 ) was observed in 58.4% of 358 individuals (86% > 75 y) [122] and that a S Na+ value ≥ 140 mMol•L −1 could be used as a first-step screening procedure for detecting underhydration in geriatric patients [99]. Similar to LOW, older adults can be encouraged to increase TWI by building upon existing habitual drinking patterns [121].…”
Section: Select Solid Foods With a High Water Contentmentioning
confidence: 99%
“…The mineral composition of salt differs depending on its origin, such as Bamboo salt, Himalaya salt, and Ba'kelalan salt. The excessive consumption of salt within a day can lead to hypernatremia [ 4 ], a condition characterized by a serum sodium concentration exceeding 145 mEq/L [ 5 ]. This can result in frequent vomiting and diarrhea, as the body aims to eliminate the excess salt.…”
Section: Introductionmentioning
confidence: 99%